Land Surface Temperature and Landuse/ Land Cover Change Variability Using Remotely Sensed Data for Sub-urban Settlements in Osun State, Nigeria - Ojolowo, Saeed K; Audu, Abiodun A; Olatubara, Charles O; Ipingbemi, Olusiyi; Odunola, Olaitan O; Omirin, Olaide J; Kasim, Oluwasinaayomi F (CSID Journal of Infrastructure Development, 2024)
Land surface temperature (LST) is an indispensable factor in studying urban climate. Ground-based measurements have been employed to quantify LST and Land Use/Land Cover Change (LULC). However, due to advancements in space technology and extensive spatial coverage, remote sensing techniques are increasingly being used to measure the intensity of LST and LULC dynamics, owing to the availability of enhanced satellite-based thermal observations of the Earth. The climatic conditions over a medium-sized city could be improved by understanding the interplay of LST and LULC. In this study, we estimated LST based on Landsat bands 4 and 5 for 1990 and 2000, band 6 for 2010, and band 10 for 2021 to reveal the interplay between the characteristics of land use and land cover and LST over Inisa and adjoining settlements. The study revealed that the maximum and minimum LST from 1990 to 2021 was 30.2°C for built-up areas and 21.1°C for farmland, respectively. Built-up areas increased from 2.5% in 1990 to 15.43% in 2021. Remotely sensed data can reveal the variability of LST and LULC to assess the climatic phenomenon. They can inform future planning to secure green and livable urban areas in this era of a changing climate.